Special Autonomy Implementation and Its Impact on the Welfare of the Society: A Short Review - I Gede Wira Adhi Darmawan (Bestuurskunde: Journal of Governmental Studies, 2022)
Indonesia has been going through long and difficult times to be an independent country. The struggles to break from colonialism out were in concordance with Indonesia's efforts to maintain and secure its territorial sovereignty. Upheavals, threats, and even separatism often arose in various parts of the country, even since the early days of Indonesia's independence. Aceh is no different. The perceived injustice in the distribution of benefits from natural resources had led to conflict in Aceh in the past. To deal with this issue, through the enactment of the Law No. 11 of 2006, the central government granted the special autonomy status for Aceh to induce peace and security, while achieving social justice within the province. The special autonomy status was also intended to accelerate the economy and improve education, quality of life, health, and infrastructure. The implementation of the special autonomy and how it contributes to the improvement of the welfare of the Aceh residents are critical and interesting to analyze. In this study, the “welfare” was analyzed based on four aspects of analysis: (1) poverty alleviation, (2) unemployment alleviation, (3) Human Development Index (HDI), and (4) Gini Ratio. The study adopted a qualitative exploratory research design, in which data were derived from analysis of secondary sources obtained through literature review. The results of the study showed that Aceh was heavily dependent on the Special Autonomy Fund. The Aceh Provincial Government set seven priority sectors: infrastructure, economic empowerment, poverty alleviation, education, social, health, and Aceh privileges. Furthermore, other than improving the Gini Ratio, the Aceh special autonomy fund has had a positive impact on the welfare of the Acehnese in general.